The distinctive attributes of registered nurses in a South African military context - April, Karen Ann (University of the Free State, 2021)
Registered nurses who work in the military have the dual role of being both a soldier and a nurse. This unique situation has prompted research about the attributes necessary for them to fulfil their roles. Besides providing general day-to-day nursing care, the reality of unrest in South Africa, terrorism, natural and human-made disasters, and deployment has led to the question of whether South African military nurses have the attributes to manage these added demanding and stressful situations. The differences between the uniqueness of military nursing in relation to civilian counterparts in South Africa are not well reflected in literature. The question was thus posed: “What are the distinctive attributes of registered nurses in a South African military context?” Since little is known or understood about the distinctive attributes of military nurses, the researcher selected a qualitative research approach through which data could be obtained from registered nurses who experience the challenges of working in the South African military context on a daily basis. The study was conducted at one specific military healthcare institute. The accessible population included 90 registered nurses at the specific military healthcare institute. The researcher used the nominal group technique (NGT) to obtain nominal and descriptive data about the distinctive attributes of registered nurses within the South African military context. The inclusion criteria for the groups were as follows: • Being a professional nurse registered with the South African Nursing Council; • Having two or more years’ experience of working within the South African military context; and • Being available to participate in the study; e.g., not being deployed during the period of data collection. To gather sufficient and relevant data, two NGT discussions were conducted. The researcher analysed the various sets of data by using six of the seven steps to analyse the data from multiple nominal groups as described by Van Breda (2005:4-12). The results of this research study indicate that the general characteristics of military nurses can be categorised as multi-skilled, military discipline, resilience, physical fitness, occupational respect, compliance, and military etiquette. Fostering and cultivating these attributes among registered nurses in the South African military healthcare context is important to ensure that the calibre of nurses meets the required standard in order to achieve the organisation’s goals.
Dissertation (M.Soc.Sc. (Nursing))--University of the Free State, 2021
Keywords: Soldiers as nurses; Military nurses -- Job stress; Military healthcare; Registered nurses